2020
DOI: 10.1200/jco.2020.38.15_suppl.e24046
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and sociodemographic predictors of mobile health applications ownership among cancer survivors.

Abstract: e24046 Background: The transition of cancer patients from patients to survivors is challenging. Cancer survivors often experience chronic physical, social and mental health needs which remain largely unmet. Due to the growing population of cancer survivors and limited resources available to address their needs, mobile health applications (apps) have emerged to help cancer patients in assuming their new role as survivors. Here, we explored the prevalence and sociodemographic predictors of mobile health apps ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…e results of the study also revealed that patients with diabetes at different developmental stages differ in their subjective understanding of their own characteristics and disease characteristics, as well as in their ability to manage objective and self-information cognition and regulatory processing and that the degree of familiarity with the use of differentiated diabetes mHealth monitoring and software development needs and the degree of decision support power vary accordingly. e study further identified three core dimensions of cognitive management, motivation, and decision support power as required for software designers of differentiated diabetes product frameworks [12]. Yang's development team provided such a mobile telediagnosis medical system on an android-based mobile device platform.…”
Section: Review Of Domestic Studiesmentioning
confidence: 99%
“…e results of the study also revealed that patients with diabetes at different developmental stages differ in their subjective understanding of their own characteristics and disease characteristics, as well as in their ability to manage objective and self-information cognition and regulatory processing and that the degree of familiarity with the use of differentiated diabetes mHealth monitoring and software development needs and the degree of decision support power vary accordingly. e study further identified three core dimensions of cognitive management, motivation, and decision support power as required for software designers of differentiated diabetes product frameworks [12]. Yang's development team provided such a mobile telediagnosis medical system on an android-based mobile device platform.…”
Section: Review Of Domestic Studiesmentioning
confidence: 99%